Investigating and Categorizing the Concept of Flexibility in Mobile Interior Spaces: The Case Study of Yacht Interior Spaces - Akyalçın, Betül (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The thesis examined the two main concepts that are flexibility and mobility. These concepts might exist in various areas of the life. Hence, this survey set out to investigate the flexible design solutions in interior design of mobile spaces which are yacht spaces. The study examined certain research objectives and try to discover wheteher flexibility is a proper solution to the limited mobile spaces in the case of being noncontextual; kinds of flexible solutions in interior yacht spaces; effects, significances and roles of flexibility as a result of the integration into interior yacht spaces; functional solutions that were achieved by the flexible systems; besides the differences and similarities of flexible solutions between various yachts. Literature review was the technique to construct theoretical background within the context of qualitative research method. On the other hand, field study was the technique within the context of quantitative research method. There were 30 cases in the field study that has chosen from ‘‘32. International Istanbul Boat Show- Marintürk Istanbul City Port’’ in Pendik/ Istanbul. The survey was finalized that, interior yacht spaces have numerous flexible solutions. These approaches respectively were divided into three headings according to the categorization of flexibility as modular systems, movable systems and foldable systems. In addition, all kinds of flexibility approaches have different categorie in their own. The study revealed that, there are 23 type of flexible solutions within 27 type in interior yacht spaces. The flexible solutions affect interior of yachts at 10 beneficial points. Furthermore, the flexible approaches are effective on 8 functions in interior yacht space. Besides, study also concluded that smaller yachts have more flexible solution then the bigger yachts. The results shows that in yacht interiors there are foldable systems firstly, movable systems secondly and modular systems lesser compared to the other two systems. The flexible approaches are effective on various functions such as sitting, eating – drinking, sleeping, storage, watching TV, sunbathing and bathing. Keywords: Interior Design / Flexible Design /Flexibility/ Mobile Space / Interior Yacht Space

ÖZ: Bu tez esneklik ve hareketlilik olmak üzere iki temel kavram çerçevesinde kurgulanmıştır. Bu iki kavram aynı zamanda yaşamın birçok alanında da kullanılmaktadır. Bu araştırma esnek çözümleri mobil mekânlarda; yat iç mekânlarını örneklem alarak inceler. Tez, esneklik kavramının kısıtlı mobil mekanlar için uygun bir çözüm olup olmadığını; yat iç mekanlarında esnek çözümlerin çeşitlerini; esnek çözümlerin yat iç mekanlarındaki etkilerini, önemi ve rolünü; esnek çözümlerin yat iç mekanlarındaki gerekliliğini; esnek sistemler sayesinde elde edilen esnek çözümleri; ayrıca farklı boyutlardaki yat iç mekanlarında ki esnek çözümlerin benzerlik ve farklılıklarını ortaya çıkarmaya çalışarak inceler. Nitel araştırma yöntemi kapsamında, teorik altyapıyı oluşturmak için literatür taraması tekniği kullanılmıştır. Öte yandan, alan araştırması tekniği nicel araştırma yöntemi kapsamında ele alınmıştır. Araştırma için 30 adet yat iç mekânı Pendik/ İstanbul da gerçekleşen ‘‘32. Uluslararası İstanbul Boat Show - Marintürk Istanbul City Port’’ fuarında sergilenen yatlar arasından belirlenmiştir. Araştırma, yat iç mekânlarında birçok farklı esnek çözümün tespit edilmesi ile sonuçlanmıştır. Araştırma, esneklik kavramına özgün bir sınıflandırma önerir ve alan çalışması bu sınıflandırma çerçevesinde yürütülür. Sınıflandırma modüler sistemler, hareketli (mobil) sistemler ve katlanabilen sistemler olarak 3 başlık altında kurgulanmıştır. Ayrıca, tüm esnek yaklaşım çeşitleri kendi içlerinde farklı kategoriler barındırmaktadır. Araştırma sonucunda, yat iç mekanlarında, sınıflandırmada önerilen 27 çeşit esnek çözümden 23’ü tespit edilmiştir. Esnek çözümler yat iç mekanlarında 10 farklı noktada ve 8 işlev üzerinde etkili olmuştur. Çalışma aynı zamanda küçük yatların büyük yatlardan daha fazla esnek çözümler içermesiyle sonuçlanmıştır. Sonuçlara göre, yat iç mekanlarında en çok katlanabilen sistemler, ikinci olarak hareket edebilen sistemler ve en az ise modüler sistemlerin kullanıldığı tespit edilmiştir. Esnek çözümler oturma, sırasıyla yeme – içme, uyuma, depolama, TV izleme, güneşlenme ve banyo yapma gibi bir takım işlevlere çözüm getirmektedir.. Anahtar Kelimeler: İç Mekân Tasarımı / Esnek Tasarım / Esneklik / Mobil Mekân / Yat İç Mekânı
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2015. Supervisor: Assoc. Prof. Dr. Nil Paşaoğluları Şahin.
Keywords: Interior Architecture; Interior Design; Interior Architecture - Mobile Interior Spaces; Yachts - Furniture, equipment, etc.--Ship decoration and design; Flexible Design; Flexibility; Mobile Space; Interior Yacht Space